DNA Nanogels To Snare Carcinogens: A Bioinspired Generic Approach with High Efficiency. Issue 40 (1st September 2016) - Topuz, Fuat; Singh, Smriti; Albrecht, Krystyna; Möller, Martin; Groll, Jürgen
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are combustion‐related pollutants and are ubiquitous in the environment, including in sources of drinking water. Upon contact with DNA, stable PAH–DNA adducts form rapidly as the first step towards their toxic effects. In this work, we prepared hydrophilic DNA nanogels to exploit this generic complexation process as a biomimetic scavenging method. This approach relies on interaction between PAHs and the complete network that constitutes the water‐swollen nanogels, and is not restricted to interfacial adsorption. Up to 720 μg of PAH per gram of DNA nanogel are taken up, meaning that 1 mg of DNA nanogel is sufficient to purify a liter of water containing the critical PAH concentration for cancer risk (600 ng L −1 ). As a result of short diffusion pathways, PAH uptake is rapid, reaching 50 % loading after 15 minutes. Beyond PAHs, DNA nanogels may be useful for the generic detoxification of water containing genotoxins, since most known molecules that strongly associate with DNA are mutagenic. Abstract : Take it away : DNA nanogels were developed as a biomimetic scavenging agent by exploiting the generic complexation of DNA with polycyclic aromatic hydrocarbons (PAHs). Up to 720 μg of PAH per gram of DNA nanogel are taken up and the uptake is rapid, reaching 50 % loading after 15 minutes. Beyond PAHs, DNA nanogels may be useful for the generic removal of genotoxins from water, since most known molecules that strongly associate with DNA are mutagenic.